Indicador de reputación para garantizar la seguridad de la interacción semántica entre objetos inteligentes del IoT mediante DAG y criptografía AES: Indicador de reputación para garantizar la seguridad de la interacción semántica entre objetos inteligentes del IoT mediante DAG y criptografía AES - Díaz-Santacruz, Carlos-Andrés; Niño-Zambrano, Miguel-Angel; Zárate-Guevara , Daniel-Guillermo; Bulla-Ortega , Samuel-Yesid (Revista Científica, 2024)
Security in semantic interaction environments of smart objects is a growing area of research, as these types of networks can be compromised by malicious nodes or by the loss of reliability of certain nodes due to various reasons. In recent years, research has progressed in the development of reputation models that allow an IoT node to evaluate the reliability of other nodes based on information provided by the network itself. This research proposes a reputation model for IoT smart objects, based on two promising technologies: the use of Directed Acyclic Graphs (DAG) and AES cryptography. These technologies are integrated with the goal of enhancing the security of shared information without compromising scalability in increasingly complex semantic interaction environments. Preliminary results suggest that the proposed solution increases the security level of the network, with a moderate impact on its performance.